Supplementing Household Income through Self-Supply and Exchange: The Case of a Multiple-Exchange Fair in Mexico City, 2016. - Campuzano, Oscar; Ayvar, Francisco Javier (PSL Quarterly Review, 2020)
For approximately 40% of Mexican households, income alone is insufficient to meet basic expenses. As a result, some families fulfill their needs through self-supply, the practice of producing goods either for direct consumption or eventual exchange. This paper demonstrates the effects that the self-supply practice has on household savings. The authors find that the practice of multiple exchange, which includes a combination of exchange, production, and self-supply, is a key mechanism that enables Mexican households to better meet their needs. Data from a survey given to participants of a trade-and-exchange fair in Mexico City in 2016 was used; the participants’ self-supply levels exceeded Mexico’s self-supply average, positively influencing their monetary savings. Download appendix online